Kajian terhadap penggunaan teknologi maklumat di kalangan pensyarah Politeknik Kota Kinabalu, Sabah : ke arah penghasilan garis panduan ABM berasaskan teknologi maklumat - Wang, Joan Yee Juen (2002)
New technologies have infiltrated workplaces, homes and very soon schools as well. Computers, CD-ROM drives, digital videodisc players, modems and scanners will be available in every school in the near future just like televisions, radio cassette players and overhead transparency projectors are at the moment. The new technologies together with sophisticated interactive and participative multimedia software will require a radical change in the approach of teaching and learning in classrooms. The change in the role of teachers in these technology-rich classrooms will have an enormous impact on them. There for, a study was conducted to investigate the used of information technology among the lecturers at Polytechnic Kota Kinabalu, Sabah. A questionnaire was used to obtain the data needed for this research. Since the finding showed that the used of information technology among the lecturers at Polytechnic Kota Kinabalu is low there fore another purpose of this study is to determine the usage force of the product, which had been developed in order to solve the problem of lack of IT usage among the lecturers. Analysis of score mean showed that most of the respondents were interested with the product. Lastly, it is hope that through this study, The Ministry Of Education and the institution itself will have a better view on how far had the technology information been infiltrated in the institution. Action then can be carried out to improve or to enhance the usage of information technology among the lecturers